Experimental study on ferritic stainless steel simply supported and continuous beams. (March 2016) - Arrayago, I.; Real, E.
Abstract: Development of efficient design guidance for stainless steel structures is key for the increased use of this corrosion-resistant material by considering both nonlinear behaviour and strain hardening into resistance prediction expressions, together with the moment redistribution in indeterminate structures. With the aim of analysing the bending moment redistribution capacity of ferritic stainless steel beams, a comprehensive experimental programme on continuous beams is presented. These tests contribute to the assessment of EN1993-1-4 specifications, where no plastic design is allowed, and the classical and new plastic design methods available in the literature for indeterminate stainless steel structures. Four three-point and eight four-point bending tests are also reported for the assessment of current codified and revised cross-sectional classification limits, analysing the different methods for the prediction of the ultimate bending capacities of ferritic hollow sections. Additional test results reported by other authors in different stainless steel grades and carbon steel are also studied and presented. The analysis indicates that Class 1 cross-sectional classification limits are too optimistic for ferritic stainless steels and further research is needed for the extension of plastic design to these grades, although promising predictions of ultimate loads are obtained for austenitic and lean duplex stainless steels. Highlights: Simply supported bending tests on ferritic stainless steel RHS and SHS are described. Continuous beam tests on ferritic stainless steel RHS and SHS are presented. Different design methods and global plastic analysis are assessed. Other stainless steel and carbon steel test results are compared.